FAKTOR UTAMA KEBERHASILAN PESERTA DIDIK DALAM MENGUASAI STANDAR KOMPETENSI - Yazidul Busthomi (JURNAL PUSAKA, 2018)
Subject competency standards can be defined as "statements about knowledge, skills and attitudes that must be mastered, and the level of mastery that is expected to be achieved in learning a subject". The competency standard is a framework that explains the basic development of a structured learning program. The subject competency standard is also the focus of the assessment, so the curriculum development process is the focus of the assessment, although the curriculum contains more of the knowledge, skills and attitudes document than evidence to show that learners who have learned have early knowledge and skills. The main factors of successful learners in mastering the subject competency standard are as follows: learners’ high intelligence level, motivation, interest in learning, their present at school, their health, and well attitude, as well as attention from their parents. Meanwhile, teachers should use appropriate methods for their learners, master learning strategies, and be professional as teachers. Keywords: Success, Learners, Competencies